Jawapan

2015-10-08T01:42:18+08:00
3x(2 -x) = 4(x -2)

6x -3x^2 = 4x -8

3x^2 -6x +4x -8 = 0

3x^2 -2x -8 = 0

(3x +4)(x -2) = 0

3x +4 = 0
3x = -4
x = -4/3

x -2 = 0
x = 2
terima kasih sekali lagi kerana sudi menolong untuk menyelesaikan soalan matematik
sama sama
2015-10-08T12:48:36+08:00
3x (2-x) = 4(x-2)
6x - 3x² = 4x - 8
-3x² + 6x - 4x + 8 = 0
-3x² + 2x + 8 = 0

3x² - 2x - 8 = 0
$\begin{align} \ \frac{(3x-6)(3x+4)}{3} &=0 \\ \frac{3(x-2)(3x+4)}{3}&= 0 \\ (x-2)(3x+4)&=0\end{align}
x - 2 = 0        atau      3x + 4 = 0
    x₁ = 2                            x₂ = -4/3